2019
DOI: 10.1186/s12935-019-0810-5
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1β cooperating with FOXA2 inhibits proliferation and migration of breast cancer cells

Abstract: Background: Breast cancer is one of the most common malignancy among females from the worldwide cancer incidence statistics. Peroxisome gamma coactivator-1β (PGC-1β) has long been identified to be involved in this type of tumorigenesis. However, the mechanisms of PGC-1β in human breast cancer have not been fully understood and the function requires to be further elucidated. Methods: mRNA and protein expression of PGC-1β and FOXA2 in breast cancer tissues and cell lines were determined by qRT-PCR and Western Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…To investigate the downstream event of CD44, a human cancer stem cell RT 2 Profiler PCR Array was applied to MDA-MB-231 CD44 knockdown cells. We discovered that the mRNA levels of various genes were upregulated in CD44 knockdown cells, and we focused on FOXA2, which has been reported to inhibit epithelial to mesenchymal transition in breast cancer [ 24 , 25 , 45 ] ( Figure 2 a; Figure S2a ). Next, we confirmed our stem cell array results by Western blot ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the downstream event of CD44, a human cancer stem cell RT 2 Profiler PCR Array was applied to MDA-MB-231 CD44 knockdown cells. We discovered that the mRNA levels of various genes were upregulated in CD44 knockdown cells, and we focused on FOXA2, which has been reported to inhibit epithelial to mesenchymal transition in breast cancer [ 24 , 25 , 45 ] ( Figure 2 a; Figure S2a ). Next, we confirmed our stem cell array results by Western blot ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, FOXA2 has been reported to inhibit mesenchymal transition in breast cancer through E-cadherin and ZEB-1 regulation [ 24 ]. Additionally, it has been found that FOXA2 interacts with other proteins to inhibit the proliferation and migration of breast cancer cells [ 25 , 45 ]. However, FOXA2 mRNA has also been reported to be associated with relapse in basal-like breast carcinoma [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental results have confirmed that PGC1β was significantly overexpressed in BC. Moreover, PGC1β could promote proliferation and migration while inhibiting the apoptosis of BC cells, suggesting it to have a tumor-promoter role in BC [20][21][22][23]. Several studies have shown that PPARγ is involved in inflammation, lipid metabolism, glucose homeostasis, and tumorigenesis [30,31].…”
Section: Ppar Researchmentioning
confidence: 99%
“…FOX-O3/PGC1β signaling axis was proved essential to sustain the pancreatic ductal adenocarcinoma cancer stem cell properties [19]. Specifically, PGC1β was proved significantly overexpressed in BC and could inhibit the apoptosis of BC cells via the mTOR signaling pathway [20,21]. PGC1β regulates HER2-overexpressing BC cell proliferation by metabolic and redox pathways [22].…”
Section: Introductionmentioning
confidence: 99%
“…They are well-established as master regulators of oxidative phosphorylation and fatty acid oxidation gene expression and are highly expressed in oxidative tissues such as brown adipose tissue, heart, kidney, skeletal muscle, and brain [19,20]. The PPARGC1 family has been reported to play an important role in cancer progression by promoting the expression of antioxidant genes, regulating the expression of vascular endothelial growth factor, and promoting glucose metabolism and adipogenesis [21][22][23]. Increased expression and activity of PPARGC1A in cancers of lung, prostate, cervical, breast, colon, and melanoma promoted cancer cell progression and chemoresistance [21,24].…”
Section: Introductionmentioning
confidence: 99%